Pengaruh Indeks Harga Saham Gabungan, Kurs, Jakarta Islamic Index, dan Covid-19 Terhadap Reksadana Saham Syariah - Mochlasin Mochlasin; Saiful Anwar; Fiona Sita Salsabila; Muhammad Ali Faisal (ITB AAS INDONESIA Surakarta, 2023)
Early in 2020 the world was surprised by the presence of a dangerous virus that attacks human breathing with the name corona virus or covid-19. The virus caused a world-scale pandemic that caused the world economy to experience shocks such as declining investment. There are several forms of investment such as sharia stock reksdana. Sharia stock mutual funds also experienced a decrease in the value of their assets during the beginning of the pandemic. There are several variables that can be the influence of declining asset values such as composite stock price index, exchange rate, and JII. The purpose of this research is to determine the Effect of Composite Stock Price Index, KURS, Jakarta Islamic Index, and Covid-19 on the Net Asset Value of Sharia Stock Mutual Funds (Trim Syariah Stock Case Study) during the covid-19 pandemic. The samples used in this study numbered 75 with sampling techniques using purposive sampling. The analysis method used is time series data regression. The results showed that the variables IHSG, JII, and Covid-19 had a significant positive effect on NAB Mutual Fund sharia stocks. Variable exchange rates have no effect on NAB Sharia stock mutual funds.